2019
DOI: 10.2478/fhort-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of a library of miRNA in gold-coloured mutant leaves of Ginkgo biloba L.

Abstract: To gain insights into the regulatory networks of miRNAs related to golden colour formation in Ginkgo biloba leaves, we constructed an sRNA library of golden-green striped mutant leaves. A total of 213 known miRNAs comprising 54 miRNA families were obtained, and 214 novel miRNAs were identified in the mutant leaves. We further constructed a normal green leaf sRNA library as a control and compared the expression of miRNAs between mutant and normal leaves. We found 42 known and 54 novel differential expression ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Li et al. found that the miR396g gene targeting chloroplast development and hormone metabolism in Ginkgo biloba leaves regulates leaf color ( Li et al., 2019 ). We predicted through correlation analysis that miR160b targeted ApSUS , miR396g targeted ApUGP2 , and miR6300 targeted ApUFGT .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. found that the miR396g gene targeting chloroplast development and hormone metabolism in Ginkgo biloba leaves regulates leaf color ( Li et al., 2019 ). We predicted through correlation analysis that miR160b targeted ApSUS , miR396g targeted ApUGP2 , and miR6300 targeted ApUFGT .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a single miRNA can target multiple genes, or many miRNAs can regulate a single gene, suggesting the functional divergence of these miRNAs [ 10 ]. On average, every miRNA has 7, 19, and 17 target genes in Cavendish bananas, Ginkgo biloba, and Japanese apricot, respectively [ 2 , 10 , 49 ]. In our study, 40 percent of miRNAs targeted 91 to 110 genes and most miRNAs had more than 40 target genes.…”
Section: Discussionmentioning
confidence: 99%
“…There are many environmental factors that can cause DNA damage in living organisms, such as ultraviolet, ionizing radiation, alkylating agents, base analogs, and many more. If DNA damage is not rapidly and accurately repaired, it can lead to permanent genetic changes that significantly alter the organisms’ genetic and phenotypic characteristics [ 1 , 2 ]. Extensive DNA damage can even cause chromosomal instabilities resulting in the death of cells and/or the whole organism [ 3 ].…”
Section: Introductionmentioning
confidence: 99%